2-18F-fluoro-2-deoxyglucose positron emission tomography in delirium. Issue 11 (November 2017) - Haggstrom, Lucy R; Nelson, Julia A; Wegner, Eva A; Caplan, Gideon A
Delirium is a common, serious, yet poorly understood syndrome. Growing evidence suggests cerebral metabolism is fundamentally disturbed; however, it has not been investigated using 2- 18 F-fluoro-2-deoxyglucose (FDG) positron emission tomography (PET) in delirium. This prospective study thus explored FDG PET patterns of cerebral glucose metabolism in older inpatients with delirium. A particular emphasis was on the posterior cingulate cortex (PCC), a key region for attention, which is a central feature of delirium. Delirium scans were compared with post-delirium scans using visual analysis and semi-quantitative analysis with NeuroQ; 13 participants (8 female, median 84 y) were scanned during delirium, and 6 scanned again after resolution. On visual analysis, cortical hypometabolism was evident in all participants during delirium (13/13), and improved with delirium resolution (6/6). Using NeuroQ, glucose metabolism was higher post-delirium in the whole brain and bilateral PCC compared to during delirium ( p < 0.05). Greater metabolism in both PCCs correlated with better performance on a neuropsychological test of attention, the WAIS-IV Digit Span Test forwards, and with shorter delirium duration. This research found widespread, reversible cortical hypometabolism during delirium and PCC hypometabolism was associated with inattention during delirium.